Influence of molecular structure on the adsorption of surfactants at water/air interface - Le, Ngoc Thu (Curtin University, 2012)
Surfactants are widely use in our daily activities such as in mineral separation, water purification, petroleum refining/processing, etc. Surfactants behaviour at the gas/liquid interface is one of the interesting research fields for both fundamental and practical applications. This thesis focused on fundamental studies of the influence of surfactant molecular structure on its adsorption behaviour as single or mixture form.A systematical study of equilibrium adsorption of alcohols and alkyltrimethylammonium bromide with different chain length and branching structure was conducted by Wilhelmy plate method. Theoretical models were applied for analyzing their adsorption activities and be utilized as the quantitative tools for evaluating the influence of molecular structure on their interfacial activities. The results showed that the longer chain length of molecule would have a higher surface activity. Moreover, the branching structure of the molecule has a lower capacity than its straight chain isomer in arranging at the interface.When mixing branching molecule alcohol methyl isobutyl carbinol with Cetyl trimethylammonium bromide or 1-octanol, a positive synergism was observed, this finding has not been reported before. However, the equilibrium adsorption of mixture of straight chain isomer alcohol (1-hexanol) with C16TAB was described well by the two general models in the literature. The observation of the positive synergism is an initial evidence for the influence of bulky structure of molecule on the equilibrium adsorption of surfactant mixture.A simple equation replaced the currently applied isotherm was integrated with dynamic models for analyzing the dynamic adsorption of surfactants. This new fitting approach in studying dynamic adsorption provided more reliable fitting results and better in prediction. The dynamic adsorption of bulky nonanol series and different chain length of alkyltrimethyl ammonium bromides were tested by pendant bubble and maximum bubble method, respectively. The experimental data were analyzed by this new fitting approach. The longer the chain length, the higher imbalance in the chain tail of molecule, the longer time is required for the surfactant reaching the interface.In summary, the findings of this thesis are: (1) Provide a systematical fundamental picture of molecule structure (chain length, branching tail) to equilibrium adsorption; (2) Identify a special synergism which might be caused by bulky structure of methyl isobutyl carbinol in mixture with certain surfactants; (3) Develop a simple, efficient, reliable approach in analyzing and predicting dynamic adsorption of surfactants.